Penetapan Kadar Kloramfenikol dalam Sediaan Kapsul Secara Spektrofotometri Infra Merah - Ronauli Ronauli (Program Studi S1 Farmasi, STIKES Senior, Medan, 2021)
Chloramphenicol is one type of broad-spectrum antibiotic and has been known since 1950 and has been shown to be active against gram negative and positive bacteria. According to Law Number 36 of 2009 concerning Health in paragraph 1 of article 105, it is stated that pharmaceutical preparations in the form of drugs and medicinal raw materials must meet the requirements of Indonesian Pharmacopoeia or other standard books.The purpose of this study was to determine the levels of chloramphenicol in capsules with a trade name and generic and to determine the suitability of the requirements of Indonesian Pharmacopoeia. Determination of chloramphenicol levels by Fourier Transform Infra Red (FTIR) spectrophotometry using methanol solvents in the wave number range 4000 - 650 cm-1. The results showed that chloramphenicol levels in Novachlor® capsules (95.80 ± 0.24)%; colcancetine® capsules (101.63 ± 2.17)%; kalmicetine® capsules (100.80 ± 0.009)%; chlorampenicol capsules (99.01 ± 0.29)%; hufamicetin capsules (102.60 ± 0.16)%. From the method validation, the results of the recovery test were 100.46%, RSD 0.005%, and LOD and LOQ 0.0029 mg / mL and 1.6763 mg / mL, respectively. These results indicate that the method performed shows accurate and precise results. The results of this study concluded that the determination of chloramphenicol levels can be done by Infrared Spectrophotometry and the levels of chloramphenicol capsules have met the requirements.